Modeling scenarios for water allocation in the Gediz Basin, Turkey - Kite, G.W.; Droogers, Peter; Murray-Rust, Hammond; Voogt, K. de (International Water Management Institute, 2001)
Describes the use of a distributed hydrologic model to evaluate different data scenarios. The study attempted to answer questions such as; what will happen to the basin water resources if a)there is a change in climate; b)it is decided that more water must be retained in the river for environmental reasons; c)more water is extracted for urban and industrial use; d)the timing and accounts used for water are changed?